Accuracy of robot-assisted pedicle screw placement for adolescent idiopathic scoliosis in the pediatric population. Issue 2 (June 2016) - Macke, Jeremy; Woo, Raymund; Varich, Laura
Abstract This is a retrospective review of pedicle screw placement in adolescent idiopathic scoliosis (AIS) patients under 18 years of age who underwent robot-assisted corrective surgery. Our primary objective was to characterize the accuracy of pedicle screw placement with evaluation by computed tomography (CT) after robot-assisted surgery in AIS patients. Screw malposition is the most frequent complication of pedicle screw placement and is more frequent in AIS. Given the potential for serious complications, the need for improved accuracy of screw placement has spurred multiple innovations including robot-assisted guidance devices. No studies to date have evaluated this robot-assisted technique using CT exclusively within the AIS population. Fifty patients were included in the study. All operative procedures were performed at a single institution by a single pediatric orthopedic surgeon. We evaluated the grade of screw breach, the direction of screw breach, and the positioning of the patient for preoperative scan (supine versus prone). Of 662 screws evaluated, 48 screws (7.2 %) demonstrated a breach of greater than 2 mm. With preoperative prone position CT scanning, only 2.4 % of screws were found to have this degree of breach. Medial malposition was found in 3 % of screws, a rate which decreased to 0 % with preoperative prone position scanning. Based on our results, we conclude that the proper use of image-guided robot-assisted surgery can improve the accuracy and safety of thoracic pedicle screw placement in patients with adolescent idiopathic scoliosis. This is the first study to evaluate the accuracy of pedicle screw placement using CT assessment in robot-assisted surgical correction of patients with AIS. In our study, the robot-assisted screw misplacement rate was lower than similarly constructed studies evaluating conventional (non-robot-assisted) procedures. If patients are preoperatively scanned in the prone position, the misplacement rate is further decreased.